2003
DOI: 10.3758/bf03196088
|View full text |Cite
|
Sign up to set email alerts
|

Forward and backward blocking of causal judgment is enhanced by additivity of effect magnitude

Abstract: When two causes for a given effect are simultaneously presented, it is natural to expect an effect of greater magnitude. However many laboratory tasks preclude such an additivity rule by imposing a ceiling on effect magnitude-for example, by using a binary outcome. Under these conditions, a compound of two causal cues cannot be distinguished from a compound of one causal cue and one noncausal cue. Two experiments tested the effect of additivity on cue competition. Significant but weak forward blocking and no b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 19 publications
2
38
2
2
Order By: Relevance
“…This finding is consistent with those of other recent studies with adults that suggest that blocking is either absent or greatly reduced when pretraining is nonadditive (Beckers et al, 2(X)5;Lovibond et al, 2003). Nevertheless, we recognize that it is possible for blocking to occur after nonadditive pretraining conditions, particularly under forward presentation conditions, (Beckers et al, 2005;Lovibond et al, 2003), and indeed backward and forward blocking has previously been reported after nonadditive pretraining conditions in a study of 5-year-olds (McCormack et al, 2009). This raises the question of whether a reasoning account is appropriate to explain all instances of this cue competition effect.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is consistent with those of other recent studies with adults that suggest that blocking is either absent or greatly reduced when pretraining is nonadditive (Beckers et al, 2(X)5;Lovibond et al, 2003). Nevertheless, we recognize that it is possible for blocking to occur after nonadditive pretraining conditions, particularly under forward presentation conditions, (Beckers et al, 2005;Lovibond et al, 2003), and indeed backward and forward blocking has previously been reported after nonadditive pretraining conditions in a study of 5-year-olds (McCormack et al, 2009). This raises the question of whether a reasoning account is appropriate to explain all instances of this cue competition effect.…”
Section: Discussionsupporting
confidence: 94%
“…Demonstrations of blocking (or related phenomena) have been provided in various species (potentially including invertebrates such as snails, Acebes, Solar, Camero, & Loy, 2009, and honey bees, although see Blaser, Couvillon, & Bitterman, 2(X)6), and animal researchers would naturally be reluctant to assume that all of these species are capable of inferential reasoning. Beckers et al (2005) and Lovibond et al (2003) allow for the possibility that there may not be a single set of processes underpinning blocking, and that, even in humans, lower-level associative processes may be involved under some circumstances. However, taken together, the findings of the current study strongly suggest that explaining the effects of additivity pretraining on blocking does require invoking a role for inferential reasoning.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It may be surprising that our experiment found evidence for backward blocking (and its preventive variant), given that recovery from overshadowing is often observed in situations where backward blocking is not (Coriett et al, 2004;Larkin et al, 1998; see also Beckers, De Houwer, Pineno, & Miller, 2005;Lovibond, Been, Mitchell, Bouton, & Frohardt, 2003;. How are we to reconcile our finding (and similar findings such as Wasserman & Berglan, 1998;Wasserman & Castro, 2005) with these other findings?…”
Section: Participants "contrasting
confidence: 40%
“…In fact, one of the main strengths of this theory is based on the empirical evidence consistent with predictions regarding the circumstances in which blocking should be found and the circumstances in which blocking should be rather unlikely. Specifically, the blocking inference should be rather unlikely if (a) the relationships between cues and outcomes are arbitrary rather than causal (De Houwer, Beckers, & Glautier, 2002;Waldmann, 2000), (b) the outcomes are always present at their maximal level, and the additivity assumption cannot be applied (Lovibond, Been, Mitchell, Bouton, & Frohardt, 2003;Mitchell & Lovibond, 2002;Mitchell et al, 2005), and (c) the goal that has to be achieved at test does not encourage participants to apply the blocking inference (e.g., Beckers et al, 2005;De Houwer et al, 2007;see also De Houwer, 2009, for a review). Because our task meets all of these conditions, the observation of blocking due to the application of the blocking inference should be very improbable.…”
Section: Implications For the Inferential Theory Of Human Contingencymentioning
confidence: 99%